(untitled) (Polis (Santiago), 2018)
The author calls for a Second Independence, and for that proposes a recovery of categories and symbols from our shameful state of dependence. He describes the domination’s most recent behavior, particularly the financial domination, and the actions of resistance. Then travels from the time when the word homeland had a liberating meaning, to the time of the myth of "globalization", where it does not have any power whatsoever, and tells us that dying is also losing ways to build our identity. He postulates the need for a categorical reset, discussing the concept of empire, and rescuing the concepts of "independence" and "emancipation”. He then proposes the reformulation of the theory of dependence and concludes with a manifesto to the Latinamerican youth.